1989
DOI: 10.1002/gps.930040604
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative confusion in the elderly

Abstract: SUMMARYWith advancing age, postoperative confusion is an increasingly important problem. Its aetiology is complex and multifactorial and includes surgical factors, anaesthetic factors, preexisting medical, psychiatric or psychological problems and postoperative complications. It often prolongs hospital stay and although mental function recovers in the majority of cases, it may be followed by permanent mental impairment. Postoperative confusion may interfere with the management of the original surgical problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our previous studies 2–4 showed that old age, dementia, regular treatment with drugs having an anticholinergic effect, depression, and cerebrovascular disorders were the main risk factors for post‐operative confusion in elderly patients treated for femoral neck fractures. These ACS risk factors have also been reported after various types of surgery 20–22 …”
supporting
confidence: 54%
“…Our previous studies 2–4 showed that old age, dementia, regular treatment with drugs having an anticholinergic effect, depression, and cerebrovascular disorders were the main risk factors for post‐operative confusion in elderly patients treated for femoral neck fractures. These ACS risk factors have also been reported after various types of surgery 20–22 …”
supporting
confidence: 54%
“…Postoperative delirium may initially manifest as mild, acute confusion and worsen rapidly. Because delirium may delay patient recovery and negatively impact prognosis, the early detection or prevention of delirium is an important aspect of the postoperative nursing management of surgical patients 4 …”
Section: Introductionmentioning
confidence: 99%
“…Surgery, or anaesthesia, has frequently been implicated in the cause of delirium; general surgery, cardiac surgery and cataract surgery have been particularly studied (Whitaker, 1989). In Millar's (1981) careful pre-and postoperative study of general surgical patients, delirium was positively associated with a number of factorsabnormal electrolytes and urea, cardiovascular problems, respiratory disease, wound infection, opiate analgesia, use of intravenous infusions and insertion of a urinary catheter.…”
Section: Cost Ejfectiveness Of Treatmentmentioning
confidence: 99%